Analysis of Eye Movements in Adults with Spinal Muscular Atrophy - Marek Krivošík; Zuzana Košutzká; Marián Šaling; Veronika Boleková; Rebeka Brauneckerová; Martin Gábor; Peter Valkovič (Medicina)
Background and Objectives: Spinal muscular atrophy (SMA) is a progressive, autosomal recessive, rare neuromuscular disorder caused by a genetic defect in the SMN1 gene, where the SMN2 gene cannot sufficiently compensate. Patients experience progressive and predominantly proximal muscular weakness and atrophy. Oculomotor disorders are currently not regarded as a typical feature of SMA. The aim of this study was to determine whether oculomotor abnormalities are present in subjects with SMA and to assess a potential relationship between the oculomotor parameters and disease duration. Materials and Methods: An analysis of 15 patients with SMA type 2 and type 3 and 15 age-matched healthy controls was conducted. The oculomotor performance, including the analysis of smooth pursuit velocity gain and saccades parameters (latency, velocity, accuracy) in the horizontal and vertical directions, was compared between both groups. Results: The analysis of smooth pursuit gain in the participants revealed a marginally significant reduction between the SMA patients and the healthy controls in the horizontal direction at a frequency of 0.2 Hz (p = 0.051), but no significant differences were observed at any other frequency or direction. The vertical velocity of the saccade eye movements of the SMA patients was increased compared with the healthy subjects, which was statistically significant for the amplitude of ±10° (p = 0.030), but not for the amplitude of ±16.5° (p = 0.107). The horizontal saccade latency, saccade velocity and saccade accuracy did not differ significantly between the SMA patients and the controls. None of the oculomotor parameters were associated with disease duration. Conclusions: While certain oculomotor abnormalities, such as increased vertical saccade velocity, were observed in the SMA patients, these findings do not indicate a defining role of oculomotor impairment in SMA pathology or its clinical characteristics.